2022
DOI: 10.1007/s11103-021-01231-y
|View full text |Cite
|
Sign up to set email alerts
|

A premature stop codon in BrFLC2 transcript results in early flowering in oilseed-type Brassica rapa plants

Abstract: Author contributionsS.K., J.A.K., and H.K. derived the RILs and performed the molecular experiments; S.K., J.A.K., and D.H.K. planned the experiments and analyzed the data; S.K. and D.H.K performed transcriptome analysis; D.H.K. supervised and completed the writing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Previously, we developed a mapping population comprised of F 5 151 RILs through the crossing of ‘Chiifu’ and ‘LP08’ ( Kim et al., 2022 ). Among the 151 F 5 RILs, the seeds of 97 germinated successfully and grew well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we developed a mapping population comprised of F 5 151 RILs through the crossing of ‘Chiifu’ and ‘LP08’ ( Kim et al., 2022 ). Among the 151 F 5 RILs, the seeds of 97 germinated successfully and grew well.…”
Section: Resultsmentioning
confidence: 99%
“…trilocularis) ‘LP08’ line were used in this study. For the mapping population, 151 individuals in the F5 generation of a Brassica rapa segregating population were obtained by crossing the ‘Chiifu’ and ‘LP08’ lines in the greenhouse of Rural Development Administration of Korea as described previously ( Kim et al., 2017 ; Kim et al., 2022 ). This population was used for QTL mapping of GSL contents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several QTL mapping studies have been reported on flowering time in B. rapa and have identified QTL regions where the FLC genes were predicted as candidate genes [ 44 , 49 , 50 ]. In oilseed-type B. rapa , QTL mapping and transcriptome analysis using ‘Chiifu’ and ‘LP08′ as parental materials indicated that BrFLC2 is a candidate gene for rapid flowering in the early flowering cultivar ‘LP08′ [ 51 ]. A major QTL on chromosome A02 was detected in several B. rapa populations with BrFLC2 as the candidate gene across different locations and seasons [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purified RNAs were used to synthesize the complementary DNA synthesis using EasyScript RTase (TransGen Biotech, China). Quantitative RT-qPCR (qRT-PCR) reactions were performed using Sol™ 2X Real-Time PCR Smart mix under the following cycling conditions: 95°C for 10 mins followed by 45 cycles of 95°C for 20s, 60°C for 25 s, and 72°C for 35 s. BrPP2Aa (Bra012474) was used as the reference gene ( Kim et al., 2022 ). qRT-PCR reactions were performed with three technical replicates by using the LineGene 9600 Plus (FQD-96A) Real-Time PCR Detection System (BioER, China).…”
Section: Methodsmentioning
confidence: 99%